Impacts of online support groups on quality of life, and perceived anxiety and depression in those with ME/CFS: a survey. Issue 2 (3rd April 2021) - Morehouse, Samantha; Schaible, Krystal; Williams, Olivia; Herlache-Pretzer, Ellen; Webster, Stacey
ABSTRACT: Background: Myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS) is a debilitating condition that can negatively affect physical and mental health [1, 2]. People with ME/CFS report lower perceived levels of social support, which further exacerbate challenges with mental health and has been linked to a higher prevalence of depression and anxiety in this population [3]. There are many mental health benefits associated with participation in in-person support groups; however, it is unknown if these benefits translate to online support groups [5]. Purpose: To examine the perceived impacts of participation in online support groups on depression, anxiety and quality of life among people with ME/CFS. Results: Responses ( n = 76) to an online survey indicated positive and negative experiences with participation in online support groups. Positive experiences included a sense of belonging, validation, supportive friendships and feelings of positively impacting others. Negative experiences included jealousy, decreased hope and optimism and disagreement regarding treatment strategies. Conclusion: Participation in online support groups was believed to decrease perceived feelings of depression and increase the quality of life in those with ME/CFS. No significant impacts on anxiety were found. Overall, participants reported engagement in online support groups to be a positive experience.